2015
DOI: 10.1093/nar/gkv812
|View full text |Cite
|
Sign up to set email alerts
|

The energetic basis of the DNA double helix: a combined microcalorimetric approach

Abstract: Microcalorimetric studies of DNA duplexes and their component single strands showed that association enthalpies of unfolded complementary strands into completely folded duplexes increase linearly with temperature and do not depend on salt concentration, i.e. duplex formation results in a constant heat capacity decrement, identical for CG and AT pairs. Although duplex thermostability increases with CG content, the enthalpic and entropic contributions of an AT pair to duplex formation exceed that of a CG pair wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 53 publications
3
55
0
1
Order By: Relevance
“…The temperature dependence of the enthalpy and entropy of DNA unfolding is therefore much more modest than that of proteins, and they do not change sign on lowering the temperature; correspondingly, one cannot expect that the DNA double helix will unfold upon cooling, as occurs for globular proteins .
Fig. 14Comparison of the partial molar heat capacities of 9, 12 and 15 base pair CG duplexes ( red ) and the same length duplexes including AT pairs ( blue ), all at the identical molar concentration of 283 µM in 150 mM NaCl, 5 mM Na-phosphate, pH 7.0 (Vaitiekunas et al 2015)
Fig. 15The partial heat capacity functions of the three considered CG DNA duplexes calculated per mole of duplex (molar heat capacity, upper panel ) and per mole of base pair (specific molar heat capacity, lower panel ), all measured at the same molarity, 230 μM, of the duplexes in 150 mM NaCl, 5 mM Na-phosphate, pH 7.4.
…”
Section: The Dna Double Helixmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature dependence of the enthalpy and entropy of DNA unfolding is therefore much more modest than that of proteins, and they do not change sign on lowering the temperature; correspondingly, one cannot expect that the DNA double helix will unfold upon cooling, as occurs for globular proteins .
Fig. 14Comparison of the partial molar heat capacities of 9, 12 and 15 base pair CG duplexes ( red ) and the same length duplexes including AT pairs ( blue ), all at the identical molar concentration of 283 µM in 150 mM NaCl, 5 mM Na-phosphate, pH 7.0 (Vaitiekunas et al 2015)
Fig. 15The partial heat capacity functions of the three considered CG DNA duplexes calculated per mole of duplex (molar heat capacity, upper panel ) and per mole of base pair (specific molar heat capacity, lower panel ), all measured at the same molarity, 230 μM, of the duplexes in 150 mM NaCl, 5 mM Na-phosphate, pH 7.4.
…”
Section: The Dna Double Helixmentioning
confidence: 99%
“…Inset the dependence of the excess enthalpy on the transition temperature, the slope of which gives an estimate of ∆ C p (Vaitiekunas et al 2015)…”
Section: The Dna Double Helixmentioning
confidence: 99%
“…Subsequent studies of thermal unfolding synthetic DNA duplexes using various physical methods led to the conclusion that the enthalpic and entropic contribution of CG basepairs significantly exceeds those of AT and both are temperature independent, i.e., unfolding of the duplex proceeds without any heat capacity increment (3)(4)(5)(6)(7). However, later detailed investigation of dissociation/association of DNA duplexes of various length and composition by highly precise differential scanning calorimetry and isothermal titration calorimetry (i.e., nano-DSC and nano-ITC (8)) showed that the enthalpy of dissociation/association of the DNA duplex is temperature dependent (i.e., proceeds with a heat capacity increment and, moreover, the enthalpic and entropic contribution of the AT pair significantly exceeds that of CG (9,10)). This is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In papers [2,8,9], as distinct from Fig. 3 and paper [10], stepwise curves were obtained for the heat capacity. In the region of near-critical temperatures in the PBD model the kinetic energy obtained from the thermostat is spent on the enchancement of the potential energy of internucleotide interaction.…”
Section: Fig 3 Specific Heat Capacity As a Derivative Of The Full Ementioning
confidence: 99%